Changes in the Use of Fuel Oil Into Electyrical Energy for Vehicles - Julianus Gesuri Daud; Christian Matindas; Nerazury Aror; Ade Juan Moses Bernadus; Miracle Keintjem (Publikasi Indonesia, 2025)
The global transportation sector faces critical challenges due to heavy dependence on fossil fuels, contributing significantly to greenhouse gas emissions and air pollution while creating economic vulnerabilities through volatile fuel prices and import dependencies. This study aims to comprehensively analyze the factors driving the transition from fuel oil to electric vehicles, evaluate the comparative advantages of electric vehicles over conventional vehicles, identify implementation challenges, and formulate innovative solutions to accelerate energy transition in the transportation sector. The research employs a qualitative approach using systematic literature review methodology, analyzing data from international energy organizations (IEA, IRENA), government policy documents, automotive industry reports, and academic journals to provide comprehensive evaluation of electric vehicle adoption trends, technological developments, and policy frameworks across different countries. Key findings reveal that electric vehicles achieve superior energy efficiency (>90%) compared to internal combustion engines (30-40%), offer significant long-term cost savings through reduced maintenance requirements and stable electricity pricing, and provide substantial environmental benefits through zero direct emissions. However, challenges include limited charging infrastructure, high initial purchase costs, and battery technology limitations in terms of storage capacity and charging time. With the supporting policies, this transition has the potential to provide long-term benefits, both for the environment and future energy security. The research implications suggest that successful electric vehicle adoption requires integrated approaches combining technological innovation, infrastructure development, and public awareness campaigns to create sustainable and efficient transportation systems for the future.